Penerapan Model Waterfall dalam Pengembangan Perangkat Lunak Pemantauan Tanaman Anggur Berbasis Mobile Menggunakan IoT - Kasliono, Kasliono; Ruslianto, Ikhwan; Erniajan, Yunita (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Unfavorable tropical climatic conditions as well as the status of grapes as not a national priority commodity, have led to high production costs and low productivity in grape cultivation in the pontianak area. So this research has The purpose to conceptualize and develop an IoT-based Android application that allows observation of grape plants in the Greenhouse. Thus, it is hoped that this application can provide solutions for farmers in monitoring plant conditions in real-time, increasing productivity, and improving the quality of grape crops in the area. In previous research, The app is technically less user-friendly, not suitable for the average users, especially farmers. Key components include an Android app, a data processing system, and sensors measuring values like air temperature, humidity, and soil moisture.. The data processing system receives data from sensors and sends it to the Android app via the internet network.. The Android app allows users to view Greenhouse environmental statistics. The research was carried out in stages, beginning with hardware and software ideation and ending with real-world testing of the application. According to the research, the system's implementation is functional, nodes can send data and be displayed on mobile applications, and tests were conducted using the black box testing method, which yielded a